2020
DOI: 10.1021/acs.langmuir.0c02370
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on Supramolecular Self-Assembly of Chlorophylls a on Chemically Reduced Graphene Oxide

Abstract: Solvent plays an important role in the surface interaction of molecules. In this study, we use "chlorophyll a", an archetypical molecule, to investigate its supramolecular selfassembly with chemically reduced graphene oxide in three different types of solvents: polar protic, polar aprotic, and non-polar. It was observed that only a polar protic solvent that can donate protons facilitates the hydrogen bonding between chlorophyll a and chemically reduced graphene oxide nanosheets in a hybrid system. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Shifts to lower wavelengths have been reported to exhibit π–π stacking and hydrophobic interactions in compounds with aromatic rings. 41 Furthermore, hydrophobic interactions of protein adsorption have been observed to shift to lower wavelengths. 42 We concluded that this blueshift indicates a hydrophobic interaction between the dyes and the porous PTFE.…”
Section: Resultsmentioning
confidence: 99%
“…Shifts to lower wavelengths have been reported to exhibit π–π stacking and hydrophobic interactions in compounds with aromatic rings. 41 Furthermore, hydrophobic interactions of protein adsorption have been observed to shift to lower wavelengths. 42 We concluded that this blueshift indicates a hydrophobic interaction between the dyes and the porous PTFE.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions with the surfaces of graphene [42][43][44][45][46][47] and graphene oxide [48][49][50][51][52] have been reported based on the p-p stacking, hydrophobic, electrostatic, and hydrogen-bonding interactions. 53,54 In the case of graphene oxide that has a variety of oxygen-containing functional groups, the electrostatic interaction is derived from the attracting force between positively and negatively charged functional groups, [49][50][51][52] while the hydrogen bonding is induced between polar functional groups and/or polar molecular moieties.…”
Section: Existing Forms Of Bqds Inside the Ac Poresmentioning
confidence: 99%
“…This provided another way to influence the adsorption properties of adsorbents by taking different types of solvents. To analyze the effect of solvent properties on adsorption, the adsorption studies were carried out by varying the self-assembled structures of biopolymers in the presence of different solvents [117]. The adsorption properties of biopolymer-modified rGO exhibited variation due to differences in self-assembled structures of chlorophills on the surface of rGO.…”
Section: Reduced Graphene Oxidementioning
confidence: 99%